Evaluación del comportamiento financiero de los proyectos de mecanismo de desarrollo limpio (mdl) en las empresas colombianas que tienen certificados de emisiones reducidas Cers - Cifuentes Camacho, Jesús David (Universidad de La Salle. Facultad de Ciencias Económicas y Sociales. Finanzas y Comercio Internacional., 2017)
Through this investigation, we sought to evaluate the financial performance in Colombian companies given the inclusion in the market for carbon credits through the Clean Development Mechanism (CDM). To do it, the projects associated in Colombia with the implementation of the CDM were identified; then, the financial performance of the companies responsible for those projects was analyzed. Finally, the reduction of CO2 emissions from these projects was evaluated and the relationship between reducing emissions and determined operating income of businesses, seeking to compare this behavior with that posed by the Environmental Kuznets Curve. After analyzing the 10 companies that meet the inclusion criteria, the relationship between the income of the company and the reduction of CO2 emissions, has the form y = k1 x2 – k2 x + c. Key words: Clean Development Mechanism, revenues, reduced emissions, Kuznets.